2022
DOI: 10.1158/1940-6207.capr-21-0555
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Metabolomics Analysis of Aspirin Treatment and Risk of Colorectal Adenomas

Abstract: Despite substantial observational and experimental evidence that aspirin use can provide protection against the development of colorectal neoplasia, our understanding of the molecular mechanisms involved is inadequate and limits our ability to use this drug effectively and safely for chemoprevention. We employed an untargeted plasma metabolomics approach using liquid chromatography with high-resolution mass spectroscopy to explore novel metabolites that may contribute to the chemopreventive effects of aspirin.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…This was suggested by the drug-induced upregulation of serotonin, aspartic acid and taurine (Figure C), in addition to an alteration in the fatty acid composition of triacylglycerols (Figure ). These observations are not novel, but in accordance with existing literature. ,,, However, the functional significance of these findings remains to be investigated in more detail.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This was suggested by the drug-induced upregulation of serotonin, aspartic acid and taurine (Figure C), in addition to an alteration in the fatty acid composition of triacylglycerols (Figure ). These observations are not novel, but in accordance with existing literature. ,,, However, the functional significance of these findings remains to be investigated in more detail.…”
Section: Resultssupporting
confidence: 90%
“…These observations are not novel, but in accordance with existing literature. 15,40,43,46 However, the functional significance of these findings remains to be investigated in more detail.…”
Section: Metabolic Alterations In Response To Acetylsalicylic Acid Ad...mentioning
confidence: 99%
“…In this case, the control group is separated from the treated samples along PC-2, while all treated groups cluster together except for a subgroup spreading along PC-1, due to biological variability. Metabolic pathways altered by DMW treatment included glycerophospholipid metabolism, which is associated with colorectal cancer risk [ 39 , 40 ]. The predominant alterations observed in AOM + DMW involved the choline-containing phospholipids, namely phosphatidylcholines and lysophosphatidylcholines, with down-regulation of glycerophosphocholine and up-regulation of lysophosphatidylcholine (1-palmitoyl-sn-glycero-3-phosphocholine, 1-octadecenoyl-sn-glycero-3-phosphocholine, 1-eicosapentaenoyl-glycero-3-phosphocholine, and 1-docosahexaenoyl-glycero-3-phosphocholine).…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with this, we found that the MEO group displayed increases in linoleic acid metabolism and elevated end products including 9,12,13-and 9,10,13-trihydroxy-10-octadecenoic acid. This metabolism typically takes place in eosinophils in pigs and contributes to skin barrier health but also has implications in colorectal cancer diagnostics and therapy (50,51).…”
Section: Discussionmentioning
confidence: 99%